A place-making approach to reclaim public space in istanbul: Transforming haliç metro köprüsü - Saputra, Sahrul Aji; Maulana, Fikri; Husni, Muhammad Fahd Diyar (The Journal of City: Branding and Authenticity, 2025)
Background: The transformation of public spaces in urban contexts requires a nuanced understanding of the interplay between architecture, cultural identity, and community needs. This study examines the Haliç Metro Köprüsü (Golden Horn Metro Bridge) in Istanbul, a structure that serves as both a critical piece of infrastructure and a contested public space within the city’s historical landscape. Positioned at the intersection of modernist design and the Golden Horn’s rich cultural heritage, the bridge has sparked debates about its impact on Istanbul's urban identity and public space. Methods: This study employs a case study approach to explore the Haliç Metro Köprüsü as a public space, using spatial analysis, stakeholder interviews, and archival research. Spatial analysis uses GIS and site observations to examine the bridge's physical characteristics, while stakeholder interviews gather perspectives on its functionality and cultural significance. Archival research reviews historical and policy documents to understand the socio-political context of the bridge's development. Findings: The study considers the challenges of reconciling the bridge’s functional role with the preservation of cultural authenticity, while also addressing the need for inclusive urban spaces that reflect the city’s diverse communities. Through a combination of spatial analysis, stakeholder perspectives, and theoretical frameworks on place identity, the research highlights strategies for reclaiming the bridge as a vibrant and culturally resonant public space. Findings emphasize the importance of integrating place-making principles into urban design processes, particularly in heritage-sensitive contexts. Conclusion: This approach not only enhances the usability and aesthetic value of public spaces but also strengthens their role as mediums for cultural expression and identity formation. Novelty/Originality of this article: The study contributes to ongoing discussions on urban authenticity and the evolving relationship between architecture, public space, and place identity.